Modeling of maternal behavior to improve the development of children under five based on social cognitive theory (SCT) and the information-motivation-behavioral skills model (IMB) - Ida Nursanti; Bhisma Murti; Sri Mulyani (Social Sciences and Humanities Open)
Child development determines the quality of human resources in the future. Mothers play a crucial role in achieving optimal child development. Several factors are related to mothers' behavior in developing children and the development of children under five, including individual, social, and behavioral factors. This study aims to examine the influence of, and relationships between, the variables of the social cognitive theory (SCT) and the information-motivation-behavioral skills (IMB) model constructs on maternal behavior in improving child development and the development of children under five years of age. This is a cross-sectional study of 400 pairs of mothers and children aged 12–59 months conducted in the Special Region of Yogyakarta. The variables are directly measured using a questionnaire based on the mother's assessment. Child development is measured by a standardized test (DDST II). The data were analyzed using path analysis with the Stata 13 application. The outcome of this study is a health promotion model that integrates the SCT and IMB in the context of maternal behavior in improving child development and the development of children under five years of age. The novelty is seen in the direct relationship between social factors and maternal behavior. Maternal behavioral factors and social factors (family support) are directly related to the development of children under five years of age. The findings of this study provide insight into how policymakers, health practitioners, ECED educators, cadres, family members, and researchers in Indonesia can promote optimal child development to improve the quality of human resources in the future. Cross-sectoral collaboration is recommended to provide guidance and training to mothers, families, and communities.